"Because we all have to grow up": supporting adolescents in Uganda to develop core competencies to transition towards managing their HIV more independently. (31st August 2020) - Lanyon, Chloe; Seeley, Janet; Namukwaya, Stella; Musiime, Victor; Paparini, Sara; Nakyambadde, Helen; Matama, Christine; Turkova, Anna; Bernays, Sarah
Abstract: Introduction: Sustaining optimal adherence is the major challenge facing adolescents living with HIV (ALHIV),  particularly in low‐resource settings, where "second‐line" is often the last accessible treatment option. We explored the knowledge and skills adolescents need in order to maintain improved adherence behaviours, and the specific ways clinicians and caregivers may support young people to do so more independently. Methods: We conducted individual, in‐depth interviews with 20 ALHIV aged 10 to 18 years in Uganda in 2017 to 2018. All participants had recently commenced second‐line treatment as part of a clinical trial. We used thematic qualitative analysis to examine adherence experiences and challenges while on first‐line therapy, as well as specific supports necessary to optimise treatment‐taking longer‐term. Results: Adherence difficulties are exacerbated by relatively rapid shifts from caregiver‐led approaches during childhood, to an expectation of autonomous treatment‐taking with onset of adolescence. For many participants this shift compounded their ongoing struggles managing physical side effects and poor treatment literacy. Switching to second‐line typically prompted reversion back to supervised adherence, with positive impacts on self‐reported adherence in the immediate term. However, this measure is unlikely to be sustainable for caregivers due to significant caregiver burden (as on first line), and provided little opportunity for clinicians to guide and develop young people's capacity to successfully adopt responsibility for their own treatment‐taking. Conclusions: As ALHIV in sub‐Saharan Africa are attributed increasing responsibility for treatment adherence and HIV management, they must be equipped with the core knowledge and skills required for successful, self‐directed care. Young people need to be relationally supported to develop necessary " adherence competencies " within the supportive framework of a gradual "transition" period. Clinic conversations during this period should be adolescent‐focussed and collaborative, and treatment‐taking strategies situated within the context of their lived environments and support networks, to facilitate sustained adherence. The disclosure of adherence difficulties must be encouraged so that issues can be identified and addressed prior to treatment failure.